P085 Relative contribution of general practices and sexual health centres in STI consultations in the netherlands. (14th July 2019) - Slurink, Isabel; Groen, Karlijn; Arguedas Flores, C; Kroone, Michelle; Hogewoning, Arjan; Ott, Alewijn; Niessen, Wim; Dukers-Muijrers, Nicole; Hoebe, Christian; Götz, Hannelore; Meima, Bram; Koedijk, Femke; et al.
Abstract : Background: Dutch estimates suggest that general practitioners (GPs) perform two-third of all STI consultations, and centres for sexual health (CSH) account for most of the remaining consultations. Yet, a comparison of consultation rates by both providers is hampered due to separate surveillance systems. We assessed the distribution of STI consultations (defined as urogenital Chlamydia trachomatis (CT) test-rates) in five regions. Methods: Data (2011 to 2016) on laboratory testing and diagnosis of urogenital CT were retrieved from CSH at public health services and laboratories in five Dutch geographical regions, aggregated by sex and age category (15–24 and 25–64 years). Regions included Amsterdam, Rotterdam, Northeast –Netherlands (N-NL), Twente and Maastricht. Using negative binomial regression, we tested for time-trends in CT test-rate per 10, 000 population at GPs and CSH within five regions and differences between the providers by region. Results: The five regions included in this study varied from mostly rural (N-NL) to highly urban (Amsterdam and Rotterdam). The relative contribution of GPs in consultation rate decreased over time in Amsterdam (60.0–47.8%), Twente (78.6–61.4%), Maastricht (59.2–47.2%), N-NL (82.4–76.9%), but not in Rotterdam (65.4–67.0%). This decrease resulted from an increase in all CSH consultation rates and a slight decrease in GP consultation rate (except for Rotterdam). Women and persons aged 25–64 years were more likely to be tested by GPs compared to CSH (relative risks of 5 regions ranging from 1.47–4.76; 1.58–7.43 respectively). All regions combined, the average yearly positivity rate was 9.2% at the GP and 10.7% at the CSH. Conclusion: GPs are still a major contributor in STI consultations, yet the CSH- contribution has increased between 2011 and 2016. In urban regions, the CSH has a considerable role, whereas in rural areas the GP provides most consultations. An explanation for differences may be CSH accessibility. Disclosure: No significant relationships.